Marjolin’s ulcer - dual lymph node metastasis with cystic degeneration: a rare presentation - Jayasree, Kasula; Quadri, S. S. S.; Rao, B. N. Umamaheswar; Kumar, D. Kiran (International Surgery Journal, 2016)
Marjolin’s ulcer is a malignant tumour developing in chronic skin lesions (burn scar, non-healing wound etc.), with a mean time period of 36 years after sustaining burns. Majority of cases reported are squamous cell carcinoma, occurring in males and involving the extremities. Surgery remains the first treatment of choice (resection with 2 cm safety margin of healthy skin for primary squamous cell carcinoma in Marjolin’s ulcers and 2.5 cm safety margin for recurrent cases). Recurrence after surgery and regional lymph node metastasis has been observed. We present a uncommon case in 55 year female with Marjolin’s ulcer following burns scar over left abdominal region, who presented as dual regional, ipsilateral axillary and inguinal lymph node metastasis with cystic degeneration.